Analytical Study of Public Service Motivation Concept (PSM) ‎and its Relationship with Public Performance (PP) ‎ - Tayeb BENAOUN (Dirassat Journal Economic Issue, 2016)
This paper addresses analytically and critically the concept of public service motivation (PSM) and the concept of public performance (PP) in some studies of occidental public work environments. However, first, we introduce the notion of public service and distinguish it from the profitable sector. The PSM concept has been developed by James Perry (1996) and he has developed an instrument for measuring it. Later, this instrument has been used in several studies; and it has become a reference in studying the notion of motivation in governmental organizations. The PSM has many links with many other organizational concepts like public performance and the degree of public service employees’ commitment, and serving both citizens and society.